Spatial distribution of roots and cracks in soils cultivated with sunflower. Issue 1 (2nd January 2018) - Cucci, Giovanna; Lacolla, Giovanni; Caranfa, Gianraffaele
ABSTRACT: The aim of this research was to investigate the spatial distribution of roots and cracks in two clay soils cropped with sunflower under different inter-row spacing in order to identify the optimal management. A latin square experimental design was applied to compare bare soil and soil cropped with sunflower, with three plant densities, obtained by keeping constant the number of plants on the row (3 plants m −1 ) and varying the row spacing (0.4, 0.6, 0.8 m). The presence of the crop and the different distance between rows influenced soil moisture content as well as the root spatial distribution and thus the structural features of cracks. Increasingly lower values of moisture were found in both soils as the distance between rows decreased; an opposite trend was observed for both root density and crack size. The volume of cracks in the soil grown with sunflower at 0.4 m row spacing was 201.4 m 3  ha −1, thus 8 times higher than the value on the bare soil and 2.5 times higher compared to the one grown at 0.8 m between rows. Optimal results in terms of root density, soil moisture and crack size were obtained with an inter-row spacing of 0.6 m.